Purification and Partial Characterization of a Hereditary Abnormal Antithrombin III Fraction of a Patient with Recurrent Thrombophlebitis - Tran, T H; Bounameaux, H; Bondeli, C; Honkanen, H; Marbet, G A; Duckert, F (Thrombosis and Haemostasis, 1980)
A relatively low heparin cofactor activity (0.60 U/ml) was observed in a patient with recurrent superficial thrombophlebitis of the left leg. However, the antigen concentration was in the normal range (1.04 U/ml) and the progressive antithrombin activity was normal. The crossed immunoelectrophoresis in presence of heparin in agarose gel separated the patient's AT-III antigen in 2 fractions with different mobilities. The patient's AT-III was purified for further characterization. The last step of the purification procedure, a heparin-agarose chromatography, led to a separation and a purification of 2 AT-III fractions with different heparin affinities: an abnormal AT-III with reduced heparin affinity and a normal AT-III with a heparin affinity similar to that of AT-III isolated from normal plasmas. Abnormal and normal AT-III share several identical properties as molecular weight, ability to form complexes with thrombin and progressive antithrombin activity.
Keywords: Antithrombin III anomaly; Heparin cofactor; Heparinagarose chromatography; Antithrombin III-thrombin complexes